Pendampingan Digitalisasi Pemasaran UMKM Batik: Dampaknya terhadap Perilaku Konsumen di Desa Kenep Sukoharjo - Dima Indah Novitasari; Faizzah Pipit Isnaini; Fitri, Fitri; Adelia Putri Irviana; Farly Fajar Saputra (Jurnal Riset Rumpun Ilmu Ekonomi, 2025)
Digital developments have encouraged batik MSME players to adjust their marketing strategies to remain relevant in today's digital era. However, most batik MSMEs in Kenep Village still rely on conventional methods so that they face obstacles in reaching consumers. This study aims to examine and compare the conditions of consumer behavior before, during, and after the implementation of marketing digitalization assistance. This research uses a descriptive qualitative approach with a comparative study method. Data were collected through non-participatory observation, interviews, and documentation on five batik MSMEs. The results showed that marketing digitalization assistance was able to improve the visual quality of products, prepare more informative descriptions, encourage consumer interaction, and expand the reach of promotions through social media and e-commerce. The implementation of digital marketing strategies through social media and e-commerce is proven to affect consumer behavior, marked by increased purchase interest, trust, and loyalty to batik products. This change makes consumers more trusting, actively provide testimonials, make repeat purchases, and recommend products to others. The implications of these findings indicate that adjustments to digital marketing strategies can have an impact on the development of local batik MSMEs